15NH4+ uptake and assimilation into amino acids is markedly reduced by elevated CO2 in Scirpus olneyi, a C3 land plant species - Felix D. Dakora; Lee-Ann C. Hayek; Bert G. Drake (South African Journal of Botany, 2024)

Genomic Diversity of Type B3 Bacteriophages of Caulobacter crescentus - Kurt T. Ash; Kristina M. Drake; Whitney S. Gibbs; Bert Ely (Current Microbiology, 2017)

Allometry data and equations for coastal marsh plants - Meng Lu; Joshua S. Caplan; Jonathan D. Bakker; J. Adam Langley; Thomas J. Mozdzer; Bert G. Drake; J. Patrick Megonigal (Ecology, 2016)
Coastal marshes are highly valued for ecosystem services such as protecting inland habitats from storms, sequestering carbon, removing nutrients and other pollutants from surface water, and providing habitat for fish, shellfish, and birds. Because plants largely determine the structure and function of coastal marshes, quantifying plant biomass is essential for evaluating these ecosystem services, understanding the biogeochemical processes that regulate ecosystem function, and forecasting tidal wetland responses to accelerated sea level rise. Allometry is a convenient and efficient technique for nondestructive estimation of plant biomass, and it is commonly used in studies of carbon and nitrogen cycles, energy flows, and marsh surface elevation change. We present plant allometry data and models developed for three long‐term experiments at the Smithsonian Global Change Research Wetland, a brackish marsh in the Rhode River subestuary of the Chesapeake Bay. The dataset contains 9,771 measurements of stem height, dry mass, and (in 9638 cases) stem width across 11 plant species. The vast majority of observations are for Schoenoplectus americanus (8430) and Phragmites australis (311), with fewer observations for other common species: Amaranthus cannabinus , Atriplex patula , Iva frutescens , Kosteletzkya virginica , Polygonum hydropiper , Solidago sempervirens , Spartina alterniflora , Spartina cynosuroides , and Typha angustifolia . Allometric relationships take the form of linear regressions of biomass (transformed using the Box‐Cox procedure) on either stem height and width, or on stem height alone. Allometric relationships for Schoenoplectus americanus were not meaningfully altered by elevated CO 2 , N enrichment, the community context, interannual variation in climate, or year, showing that a single equation can be used across a broad range of conditions for this species. Archived files include: (1) raw data used to derive allometric equations for each species, (2) reports and evaluations of the allometric equations we derived from the data, and (3) R code with which our derivations can be replicated. Methodological details of our experiments, data collection efforts, and statistical modeling are described in the metadata. The allometric equations can be used for biomass estimation in empirical and modeling studies of North American coastal wetlands, and the data can be used in ecological studies of terrestrial plant allometry.

Inter‐annual changes in detritus‐based food chains can enhance plant growth response to elevated atmospheric CO 2 - Jes Hines; Nico Eisenhauer; Bert G. Drake (Global Change Biology, 2015)
Elevated atmospheric CO 2 generally enhances plant growth, but the magnitude of the effects depend, in part, on nutrient availability and plant photosynthetic pathway. Due to their pivotal role in nutrient cycling, changes in abundance of detritivores could influence the effects of elevated atmospheric CO 2 on essential ecosystem processes, such as decomposition and primary production. We conducted a field survey and a microcosm experiment to test the influence of changes in detritus‐based food chains on litter mass loss and plant growth response to elevated atmospheric CO 2 using two wetland plants: a C 3 sedge ( S cirpus olneyi ) and a C 4 grass ( S partina patens ). Our field study revealed that organism's sensitivity to climate increased with trophic level resulting in strong inter‐annual variation in detritus‐based food chain length. Our microcosm experiment demonstrated that increased detritivore abundance could not only enhance decomposition rates, but also enhance plant growth of S . olneyi in elevated atmospheric CO 2 conditions. In contrast, we found no evidence that changes in the detritus‐based food chains influenced the growth of S . patens . Considered together, these results emphasize the importance of approaches that unite traditionally subdivided food web compartments and plant physiological processes to understand inter‐annual variation in plant production response to elevated atmospheric CO 2.

Rising sea level, temperature, and precipitation impact plant and ecosystem responses to elevated CO 2 on a Chesapeake Bay wetland: review of a 28‐year study - Bert G. Drake (Global Change Biology, 2014)
An ongoing field study of the effects of elevated atmospheric CO 2 on a brackish wetland on Chesapeake Bay, started in 1987, is unique as the longest continually running investigation of the effects of elevated CO 2 on an ecosystem. Since the beginning of the study, atmospheric CO 2 increased 18%, sea level rose 20 cm, and growing season temperature varied with approximately the same range as predicted for global warming in the 21st century. This review looks back at this study for clues about how the effects of rising sea level, temperature, and precipitation interact with high atmospheric CO 2 to alter the physiology of C3 and C4 photosynthetic species, carbon assimilation, evapotranspiration, plant and ecosystem nitrogen, and distribution of plant communities in this brackish wetland. Rising sea level caused a shift to higher elevations in the S cirpus olneyi C3 populations on the wetland, displacing the S partina patens C4 populations. Elevated CO 2 stimulated carbon assimilation in the Scirpus C3 species measured by increased shoot and root density and biomass, net ecosystem production, dissolved organic and inorganic carbon, and methane production. But elevated CO 2 also decreased biomass of the grass, S . patens C4. The elevated CO 2 treatment reduced tissue nitrogen concentration in shoots, roots, and total canopy nitrogen, which was associated with reduced ecosystem respiration. Net ecosystem production was mediated by precipitation through soil salinity: high salinity reduced the CO 2 effect on net ecosystem production, which was zero in years of severe drought. The elevated CO 2 stimulation of shoot density in the Scirpus C3 species was sustained throughout the 28 years of the study. Results from this study suggest that rising CO 2 can add substantial amounts of carbon to ecosystems through stimulation of carbon assimilation, increased root exudates to supply nitrogen fixation, reduced dark respiration, and improved water and nitrogen use efficiency.

Direct and indirect effects of elevated atmospheric CO 2 on net ecosystem production in a Chesapeake Bay tidal wetland - John E. Erickson; Gary Peresta; Kathryn J. Montovan; Bert G. Drake (Global Change Biology, 2013)
The rapid increase in atmospheric CO 2 concentrations ( C a ) has resulted in extensive research efforts to understand its impact on terrestrial ecosystems, especially carbon balance. Despite these efforts, there are relatively few data comparing net ecosystem exchange of CO 2 between the atmosphere and the biosphere ( NEE ), under both ambient and elevated C a . Here we report data on annual sums of CO 2 ( NEE net ) for 19 years on a Chesapeake Bay tidal wetland for S cirpus olneyi (C 3 photosynthetic pathway)‐ and Spartina patens (C 4 photosynthetic pathway)‐dominated high marsh communities exposed to ambient and elevated C a (ambient + 340 ppm). Our objectives were to (i) quantify effects of elevated C a on seasonally integrated CO 2 assimilation ( NEE net = NEE day + NEE night , kg C m −2 y −1 ) for the two communities; and (ii) quantify effects of altered canopy N content on ecosystem photosynthesis and respiration. Across all years, NEE net averaged 1.9 kg m −2 y −1 in ambient C a and 2.5 kg m −2 y −1 in elevated C a , for the C 3 ‐dominated community. Similarly, elevated C a significantly ( P 4 ‐dominated community, as NEE net averaged 1.5 kg m −2 y −1 in ambient C a and 1.7 kg m −2 y −1 in elevated C a . This resulted in an average CO 2 stimulation of 32% and 13% of seasonally integrated NEE net for the C 3 ‐ and C 4 ‐dominated communities, respectively. Increased NEE day was correlated with increased efficiencies of light and nitrogen use for net carbon assimilation under elevated C a , while decreased NEE night was associated with lower canopy nitrogen content. These results suggest that rising C a may increase carbon assimilation in both C 3 ‐ and C 4 ‐dominated wetland communities. The challenge remains to identify the fate of the assimilated carbon.

Enhanced Autologous Re-endothelialization of Decellularized and Extracellular Matrix Conditioned Allografts Implanted Into the Right Ventricular Outflow Tracts of Juvenile Sheep - Rachael W. Quinn; Stephen L. Hilbert; Gabriel L. Converse; Arthur A. Bert; Eric Buse; William B. Drake; Matt Armstrong; Sara J. Moriarty; Gary K. Lofland; Richard A. Hopkins (Cardiovascular Engineering and Technology, 2012)

Evapotranspiration and water use efficiency in a Chesapeake Bay wetland under carbon dioxide enrichment - JIAHONG LI; JOHN E. ERICKSON; GARY PERESTA; BERT G. DRAKE (Global Change Biology, 2010)
Wetlands evapotranspire more water than other ecosystems, including agricultural, forest and grassland ecosystems. However, the effects of elevated atmospheric carbon dioxide (CO 2 ) concentration ( C a ) on wetland evapotranspiration (ET) are largely unknown. Here, we present data on 12 years of measurements of ET, net ecosystem CO 2 exchange (NEE), and ecosystem water use efficiency (EWUE, i.e. NEE/ET) at 13:00–15:00 hours in July and August for a Scirpus olneyi (C3 sedge) community and a Spartina patens (C4 grass) community exposed to ambient and elevated (ambient+340 μmol mol −1 ) C a in a Chesapeake Bay wetland. Although a decrease in stomatal conductance at elevated C a in the S. olneyi community was counteracted by an increase in leaf area index (LAI) to some extend, ET was still reduced by 19% on average over 12 years. In the S. patens community, LAI was not affected by elevated C a and the reduction of ET was 34%, larger than in the S. olneyi community. For both communities, the relative reduction in ET by elevated C a was directly proportional to precipitation due to a larger reduction in stomatal conductance in the control plants as precipitation decreased. NEE was stimulated about 36% at elevated C a in the S. olneyi community but was not significantly affected by elevated C a in S. patens community. A negative correlation between salinity and precipitation observed in the field indicated that precipitation affected ET through altered salinity and interacted with growth C a . This proposed mechanism was supported by a greenhouse study that showed a greater C a effect on ET in controlled low salinity conditions compared with high salinity. In spite of the differences between the two communities in their responses to elevated C a , EWUE was increased about 83% by elevated C a in both the S. olneyi and S. patens communities. These findings suggest that rising C a could have significant impacts on the hydrologic cycles of coastal wetlands.

Does deep soil N availability sustain long‐term ecosystem responses to elevated CO 2 ? - DUNCAN C. McKINLEY; JULIO C. ROMERO; BRUCE A. HUNGATE; BERT G. DRAKE; JAMES P. MEGONIGAL (Global Change Biology, 2009)
A scrub‐oak woodland has maintained higher aboveground biomass accumulation after 11 years of atmospheric CO 2 enrichment (ambient +350 μmol CO 2 mol −1 ), despite the expectation of strong nitrogen (N) limitation at the site. We hypothesized that changes in plant available N and exploitation of deep sources of inorganic N in soils have sustained greater growth at elevated CO 2 . We employed a suite of assays performed in the sixth and 11th year of a CO 2 enrichment experiment designed to assess soil N dynamics and N availability in the entire soil profile. In the 11th year, we found no differences in gross N flux, but significantly greater microbial respiration ( P≤ 0.01) at elevated CO 2 . Elevated CO 2 lowered extractable inorganic N concentrations ( P =0.096) considering the whole soil profile (0–190 cm). Conversely, potential net N mineralization, although not significant in considering the entire profile ( P =0.460), tended to be greater at elevated CO 2 . Ion‐exchange resins placed in the soil profile for approximately 1 year revealed that potential N availability at the water table was almost 3 × greater than found elsewhere in the profile, and we found direct evidence using a 15 N tracer study that plants took up N from the water table. Increased microbial respiration and shorter mean residence times of inorganic N at shallower depths suggests that enhanced SOM decomposition may promote a sustained supply of inorganic N at elevated CO 2 . Deep soil N availability at the water table is considerable, and provides a readily available source of N for plant uptake. Increased plant growth at elevated CO 2 in this ecosystem may be sustained through greater inorganic N supply from shallow soils and N uptake from deep soil.

Seeing the forest for the trees: long‐term exposure to elevated CO 2 increases some herbivore densities - PETER STILING; DANIEL MOON; ANTHONY ROSSI; BRUCE A. HUNGATE; BERT DRAKE (Global Change Biology, 2009)
The effects of elevated CO 2 on plant growth and insect herbivory have been frequently investigated over the past 20 years. Most studies have shown an increase in plant growth, a decrease in plant nitrogen concentration, an increase in plant secondary metabolites and a decrease in herbivory. However, such studies have generally overlooked the fact that increases in plant production could cause increases of herbivores per unit area of habitat. Our study investigated leaf production, herbivory levels and herbivore abundance per unit area of leaf litter in a scrub‐oak system at Kennedy Space Center, Florida, under conditions of ambient and elevated CO 2 , over an 11‐year period, from 1996 to 2007. In every year, herbivory, that is leafminer and leaftier abundance per 200 leaves, was lower under elevated CO 2 than ambient CO 2 for each of three species of oaks, Quercus myrtifolia, Quercus chapmanii and Quercus geminata . However, leaf litter production per 0.1143 m 2 was greater under elevated CO 2 than ambient CO 2 for Q. myrtifolia and Q. chapmanii , and this difference increased over the 11 years of the study. Leaf production of Q. geminata under elevated CO 2 did not increase. Leafminer densities per 0.1143 m 2 of litterfall for Q. myrtifolia and Q. chapmanii were initially lower under elevated CO 2 . However, shortly after canopy closure in 2001, leafminer densities per 0.1143 m 2 of litter fall became higher under elevated CO 2 and remained higher for the remainder of the experiment. Leaftier densities per 0.1143 m 2 were also higher under elevated CO 2 for Q. myrtifolia and Q. chapmanii over the last 6 years of the experiment. There were no differences in leafminer or leaftier densities per 0.1143 m 2 of litter for Q. geminata . These results show three phenomena. First, they show that elevated CO 2 decreases herbivory on all oak species in the Florida scrub‐oak system. Second, despite lower numbers of herbivores per 200 leaves in elevated CO 2 , increased leaf production resulted in higher herbivore densities per unit area of leaf litter for two oak species. Third, they corroborate other studies which suggest that the effects of elevated CO 2 on herbivores are species specific, meaning they depend on the particular plant species involved. Two oak species showed increases in leaf production and herbivore densities per 0.1143 m 2 in elevated CO 2 over time while another oak species did not. Our results point to a future world of elevated CO 2 where, despite lower plant herbivory, some insect herbivores may become more common.

Disturbance, rainfall and contrasting species responses mediated aboveground biomass response to 11 years of CO 2 enrichment in a Florida scrub‐oak ecosystem - TROY J. SEILER; DANIEL P. RASSE; JIAHONG LI; PAUL DIJKSTRA; HANS P. ANDERSON; DAVID P. JOHNSON; THOMAS L. POWELL; BRUCE A. HUNGATE; C. ROSS HINKLE; BERT G. DRAKE (Global Change Biology, 2009)
This study reports the aboveground biomass response of a fire‐regenerated Florida scrub‐oak ecosystem exposed to elevated CO 2 (1996–2007), from emergence after fire through canopy closure. Eleven years exposure to elevated CO 2 caused a 67% increase in aboveground shoot biomass. Growth stimulation was sustained throughout the experiment; although there was significant variability between years. The absolute stimulation of aboveground biomass generally declined over time, reflecting increasing environmental limitations to long‐term growth response. Extensive defoliation caused by hurricanes in September 2004 was followed by a strong increase in shoot density in 2005 that may have resulted from reopening the canopy and relocating nitrogen from leaves to the nutrient‐poor soil. Biomass response to elevated CO 2 was driven primarily by stimulation of growth of the dominant species, Quercus myrtifolia , while Quercus geminata , the other co‐dominant oak, displayed no significant CO 2 response. Aboveground growth also displayed interannual variation, which was correlated with total annual rainfall. The rainfall × CO 2 interaction was partially masked at the community level by species‐specific responses: elevated CO 2 had an ameliorating effect on Q. myrtifolia growth under water stress. The results of this long‐term study not only show that atmospheric CO 2 concentration had a consistent stimulating effect on aboveground biomass production, but also showed that available water is the primary driver of interannual variation in shoot growth and that the long‐term response to elevated CO 2 may have been caused by other factors such as nutrient limitation and disturbance.

An oxygen‐mediated positive feedback between elevated carbon dioxide and soil organic matter decomposition in a simulated anaerobic wetland - AMELIA A. WOLF; BERT G. DRAKE; JOHN E. ERICKSON; J. PATRICK MEGONIGAL (Global Change Biology, 2007)
We examined the effects of elevated atmospheric CO 2 on soil carbon decomposition in an experimental anaerobic wetland system. Pots containing either bare C 4 ‐derived soil or the C 3 sedge Scirpus olneyi planted in C 4 ‐derived soil were incubated in greenhouse chambers at either ambient or twice‐ambient atmospheric CO 2 . We measured CO 2 flux from each pot, quantified soil organic matter (SOM) mineralization using δ 13 C, and determined root and shoot biomass. SOM mineralization increased in response to elevated CO 2 by 83–218% ( P P = 0.003). Our results (1) show that there is a positive feedback between elevated atmospheric CO 2 concentrations and wetland SOM decomposition and (2) suggest that this process is mediated by the release of oxygen from the roots of wetland plants. Because this feedback may occur in any wetland system, including peatlands, these results suggest a limitation on the size of the carbon sink presented by anaerobic wetland soils in a future elevated‐CO 2 atmosphere.

Impacts of Hurricane Frances on Florida scrub‐oak ecosystem processes: defoliation, net CO 2 exchange and interactions with elevated CO 2 - JIAHONG LI; THOMAS L. POWELL; TROY J. SEILER; DAVID P. JOHNSON; HANS P. ANDERSON; ROSVEL BRACHO; BRUCE A. HUNGATE; CHARLES R. HINKLE; BERT G. DRAKE (Global Change Biology, 2007)
Hurricane disturbances have profound impacts on ecosystem structure and function, yet their effects on ecosystem CO 2 exchange have not been reported. In September 2004, our research site on a fire‐regenerated scrub‐oak ecosystem in central Florida was struck by Hurricane Frances with sustained winds of 113 km h −1 and wind gusts as high as 152 km h −1 . We quantified the hurricane damage on this ecosystem resulting from defoliation: we measured net ecosystem CO 2 exchange, the damage and recovery of leaf area, and determined whether growth in elevated carbon dioxide concentration in the atmosphere ( C a ) altered this disturbance. The hurricane decreased leaf area index (LAI) by 21%, which was equal to 60% of seasonal variation in canopy growth during the previous 3 years, but stem damage was negligible. The reduction in LAI led to a 22% decline in gross primary production (GPP) and a 25% decline in ecosystem respiration ( R e ). The compensatory declines in GPP and R e resulted in no significant change in net ecosystem production (NEP). Refoliation began within a month after the hurricane, although this period was out of phase with the regular foliation period, and recovered 20% of the defoliation loss within 2.5 months. Full recovery of LAI, ecosystem CO 2 assimilation, and ecosystem respiration did not occur until the next growing season. Plants exposed to elevated C a did not sustain greater damage, nor did they recover faster than plants grown under ambient C a . Thus, our results indicate that hurricanes capable of causing significant defoliation with negligible damage to stems have negligible effects on NEP under current or future CO 2 ‐enriched environment.

Root biomass and nutrient dynamics in a scrub-oak ecosystem under the influence of elevated atmospheric CO2 - Alisha Lea Pagel Brown; Frank P. Day; Bruce A. Hungate; Bert G. Drake; C. Ross Hinkle (Plant and Soil, 2007)

Salinity and sea level mediate elevated CO 2 effects on C 3 –C 4 plant interactions and tissue nitrogen in a Chesapeake Bay tidal wetland - JOHN E. ERICKSON; J. PATRICK MEGONIGAL; GARY PERESTA; BERT G. DRAKE (Global Change Biology, 2007)
Elevated atmospheric carbon dioxide concentrations ([CO 2 ]) generally increase plant photosynthesis in C 3 species, but not in C 4 species, and reduce stomatal conductance in both C 3 and C 4 plants. In addition, tissue nitrogen concentration ([N]) often fails to keep pace with enhanced carbon gain under elevated CO 2 , particularly in C 3 species. While these responses are well documented in many species, implications for plant growth and nutrient cycling in native ecosystems are not clear. Here we present data on 18 years of measurement of above and belowground biomass, tissue [N] and total standing crop of N for a Scirpus olneyi ‐dominated (C 3 sedge) community, a Spartina patens ‐dominated (C 4 grass) community and a C 3 –C 4 ‐mixed species community exposed to ambient and elevated (ambient +340 ppm) atmospheric [CO 2 ] in natural salinity and sea level conditions of a Chesapeake Bay wetland. Increased biomass production (shoots plus roots) under elevated [CO 2 ] in the S. olneyi ‐dominated community was sustained throughout the study, averaging approximately 35%, while no significant effect of elevated [CO 2 ] was found for total biomass in the C 4 ‐dominated community. We found a significant decline in C 4 biomass (correlated with rising sea level) and a concomitant increase in C 3 biomass in the mixed community. This shift from C 4 to C 3 was accelerated by the elevated [CO 2 ] treatment. The elevated [CO 2 ] stimulation of total biomass accumulation was greatest during rainy, low salinity years: the average increase above the ambient treatment during the three wettest years (1994, 1996, 2003) was 2.9 t ha −1 but in the three driest years (1995, 1999, 2002), it was 1.2 t ha −1 . Elevated [CO 2 ] depressed tissue [N] in both species, but especially in the S. olneyi where the relative depression was positively correlated with salinity and negatively related with the relative enhancement of total biomass production. Thus, the greatest amount of carbon was added to the S. olneyi ‐dominated community during years when shoot [N] was reduced the most, suggesting that the availability of N was not the most or even the main limitation to elevated [CO 2 ] stimulation of carbon accumulation in this ecosystem.

Rapid root closure after fire limits fine root responses to elevated atmospheric CO 2 in a scrub oak ecosystem in central Florida, USA - FRANK P. DAY; DANIEL B. STOVER; ALISHA L. PAGEL; BRUCE A. HUNGATE; JOHN J. DILUSTRO; BRANDON T. HERBERT; BERT G. DRAKE; CHARLES R. HINKLE (Global Change Biology, 2006)
Elevated atmospheric carbon dioxide (CO 2 ) often stimulates the growth of fine roots, yet there are few reports of responses of intact root systems to long‐term CO 2 exposure. We investigated the effects of elevated CO 2 on fine root growth using open top chambers in a scrub oak ecosystem at Kennedy Space Center, Florida for more than 7 years. CO 2 enrichment began immediately after a controlled burn, which simulated the natural disturbance that occurs in this system every 10–15 years. We hypothesized that (1) root abundance would increase in both treatments as the system recovered from fire; (2) elevated CO 2 would stimulate root growth; and (3) elevated CO 2 would alter root distribution. Minirhizotron tubes were used to measure fine root length density (mm cm −2 ) every three months. During the first 2 years after fire recovery, fine root abundance increased in all treatments and elevated CO 2 significantly enhanced root abundance, causing a maximum stimulation of 181% after 20 months. The CO 2 stimulation was initially more pronounced in the top 10 cm and 38–49 cm below the soil surface. However, these responses completely disappeared during the third year of experimental treatment: elevated CO 2 had no effect on root abundance or on the depth distribution of fine roots during years 3–7. The results suggest that, within a few years following fire, fine roots in this scrub oak ecosystem reach closure, defined here as a dynamic equilibrium between production and mortality. These results further suggest that elevated CO 2 hastens root closure but does not affect maximum root abundance. Limitation of fine root growth by belowground resources – particularly nutrients in this nutrient‐poor soil – may explain the transient response to elevated CO 2 .

Elevated CO 2 increases the long‐term decomposition rate of Quercus myrtifolia leaf litter - MYRA C. HALL; PETER STILING; DANIEL C. MOON; BERT G. DRAKE; MARK D. HUNTER (Global Change Biology, 2006)
Decomposition of Quercus myrtifolia leaf litter in a Florida scrub oak community was followed for 3 years in two separate experiments. In the first experiment, we examined the effects CO 2 and herbivore damage on litter quality and subsequent decomposition. Undamaged, chewed and mined litter generated under ambient and elevated (ambient+350 ppm V) CO 2 was allowed to decompose under ambient conditions for 3 years. Initial litter chemistry indicated that CO 2 levels had minor effects on litter quality. Litter damaged by leaf miners had higher initial concentrations of condensed tannins and nitrogen (N) and lower concentrations of hemicellulose and C : N ratios compared with undamaged and chewed litter. Despite variation in litter quality associated with CO 2 , herbivory, and their interaction, there was no subsequent effect on rates of decomposition under ambient atmospheric conditions. In the second experiment, we examined the effects of source (ambient and elevated) of litter and decomposition site (ambient and elevated) on litter decomposition and N dynamics. Litter was not separated by damage type. The litter from both elevated and ambient CO 2 was then decomposed in both elevated and ambient CO 2 chambers. Initial litter chemistry indicated that concentrations of carbon (C), hemicellulose, and lignin were higher in litter from elevated than ambient CO 2 chambers. Despite differences in C and fiber concentrations, litter from ambient and elevated CO 2 decomposed at comparable rates. However, the atmosphere in which the decomposition took place resulted in significant differences in rates of decomposition. Litter decomposing under elevated CO 2 decomposed more rapidly than litter under ambient CO 2 , and exhibited higher rates of mineral N accumulation. The results suggest that the atmospheric conditions during the decomposition process have a greater impact on rates of decomposition and N cycling than do the atmospheric conditions under which the foliage was produced.

Effects of Elevated CO2 and Herbivore Damage on Litter Quality in a Scrub Oak Ecosystem - Myra C. Hall; Peter Stiling; Bruce A. Hungate; Bert G. Drake; Mark D. Hunter (Journal of Chemical Ecology, 2005)

Seventeen years of elevated CO 2 exposure in a Chesapeake Bay Wetland: sustained but contrasting responses of plant growth and CO 2 uptake - Daniel P. Rasse; Gary Peresta; Bert G. Drake (Global Change Biology, 2005)
Increased atmospheric CO 2 concentration ( Ca ) produces a short‐term stimulation of photosynthesis and plant growth across terrestrial ecosystems. However, the long‐term response remains uncertain and is thought to depend on environmental constraints. In the longest experiment on natural ecosystem response to elevated Ca , we measured the shoot‐density, biomass and net CO 2 exchange (NEE) responses to elevated Ca from 1987 to 2003 in a Scirpus olneyi wetland sedge community of the Chesapeake Bay, MD, USA. Measurements were conducted in five replicated open‐top chambers per CO 2 treatment (ambient and elevated). In addition, unchambered control plots were monitored for shoot density. Responses of daytime NEE, Scirpus plant biomass and shoot density to elevated Ca were positive for any single year of the 17‐year period of study. Daytime NEE stimulation by elevated Ca rapidly dropped from 80% at the onset of the experiment to a long‐term stimulation average of about 35%. Shoot‐density stimulation by elevated Ca increased linearly with duration of exposure ( r 2 =0.89), exceeding 120% after 17 years. Although of lesser magnitude, the shoot biomass response to elevated Ca was similar to that of the shoot density. Daytime NEE response to elevated Ca was not explained by the duration of exposure, but negatively correlated with salinity of the marsh, indicating that this elevated‐ Ca response was decreased by water‐related stress. By contrast, circumstantial evidence suggested that salinity stress increased the stimulation of shoot density by elevated Ca , which highlights the complexity of the interaction between water‐related stresses and plant community responses to elevated Ca . Notwithstanding the effects of salinity stress, we believe that the most important finding of the present research is that a species response to elevated Ca can continually increase when this species is under stress and declining in its natural environment. This is particularly important because climate changes associated with elevated Ca are likely to increase environmental stresses on numerous species and modify their present distribution. Our results point to an increased resilience to change under elevated Ca when plants are exposed to adverse environmental conditions.

Effects of elevated CO2 on foliar quality and herbivore damage in a scrub oak ecosystem - Myra C. Hall; Peter Stiling; Daniel C. Moon; Bert G. Drake; Mark D. Hunter (Journal of Chemical Ecology, 2005)

Induced Defensive Response of Myrtle Oak to Foliar Insect Herbivory in Ambient and Elevated Co2 - Anthony M. Rossi; Peter Stiling; Daniel C. Moon; Maria V. Cattell; Bert G. Drake (Journal of Chemical Ecology, 2004)

Differential effects of elevated CO 2 on acorn density, weight, germination, and predation among three oak species in a scrub‐oak forest - Peter Stiling; Daniel Moon; Graham Hymus; Bert Drake (Global Change Biology, 2004)
Much research on the effects of elevated CO 2 on forest trees has focused on quantitative changes in photosynthesis, secondary chemistry, and plant biomass. However, plant fitness responses to rising CO 2 should also include quantitative measures of reproduction, since most forest systems are recruitment limited. Until now, it has proved very difficult to grow forest trees to sexual maturity in a CO 2 ‐enriched environment. This paper is the first of its kind to address the effects of elevated CO 2 on the reproduction of hardwood trees in a natural forest. Beginning in 1996, scrub‐oak vegetation, predominantly three species of scrub‐oaks, Quercus myrtifolia , Q . chapmanii , and Q . geminata , were grown inside eight chambers with elevated CO 2 (704 parts per million (ppm)) and eight with ambient CO 2 (379 ppm) at Kennedy Space Center, Florida. In elevated CO 2 , acorn production increased significantly for the dominant species Q . myrtifolia and for Q . chapmanii , but it did not increase for the subdominant, Q . geminata . Acorn weight, germination rate, and predation by weevils were unaffected by CO 2 . Thus, recruitment of some forest tree species into the Florida scrub‐oak community is likely to be accelerated in an atmosphere of increased CO 2 . However, because the acceleration of recruitment differs among species, over the long term, Q. myrtifolia and Q. chapmanii will be favored over Q. geminata and this is likely to change patterns of species diversity.

Elevated CO 2 decreases leaf fluctuating asymmetry and herbivory by leaf miners on two oak species - Tatiana Cornelissen; Peter Stiling; Bert Drake (Global Change Biology, 2004)
Fluctuating asymmetry (FA) represents small, random variation from symmetry in otherwise bilaterally symmetrical characters. Significant increases in FA have been found for several species of plants and animals in response to various stresses, including environmental and genetic factors. In this study, we investigated the effects of elevated CO 2 on leaf symmetry of two oak species, Quercus geminata and Q. myrtifolia , and the responses of three species of leaf miners and one gall‐making species to random variation in leaf morphology. Leaf FA decreased with an increase in CO 2 concentration. There were fewer asymmetric leaves and lower levels of asymmetry on leaf width and leaf area on elevated CO 2 compared with ambient CO 2 . Leaf miners responded to leaf asymmetry, attacking asymmetric leaves more frequently than expected by chance alone. Differences in secondary chemistry and nitrogen (N) content between symmetric and asymmetric leaves may be responsible for these results due to lower levels of tannins and higher levels of N found on asymmetric leaves of Q. myrtifolia and Q. geminata .

Effects of elevated atmospheric CO 2 on net ecosystem CO 2 exchange of a scrub–oak ecosystem - Graham J. Hymus; David P. Johnson; Sabina Dore; Hans P. Anderson; C. Ross Hinkle; Bert G. Drake (Global Change Biology, 2003)
We report the results of a 2‐year study of effects of the elevated (current ambient plus 350 μmol CO 2 mol −1 ) atmospheric CO 2 concentration ( C a ) on net ecosystem CO 2 exchange ( NEE ) of a scrub–oak ecosystem. The measurements were made in open‐top chambers (OTCs) modified to function as open gas‐exchange systems. The OTCs enclosed samples of the ecosystem (ca. 10 m 2 surface area) that had regenerated after a fire, 5 years before, in either current ambient or elevated C a . Throughout the study, elevated C a increased maximum NEE ( NEE max ) and the apparent quantum yield of the NEE ( φ NEE ) during the photoperiod. The magnitude of the stimulation of NEE max , expressed per unit ground area, was seasonal, rising from 50% in the winter to 180% in the summer. The key to this stimulation was effects of elevated C a , and their interaction with the seasonal changes in the environment, on ecosystem leaf area index, photosynthesis and respiration. The separation of these factors was difficult. When expressed per unit leaf area the stimulation of the NEE max ranged from 7% to 60%, with the increase being dependent on increasing soil water content ( W soil ). At night, the CO 2 effluxes from the ecosystem ( NEE night ) were on an average 39% higher in elevated C a . However, the increase varied between 6% and 64%, and had no clear seasonality. The partitioning of NEE night into its belowground ( R below ) and aboveground ( R above ) components was carried out in the winter only. A 35% and 27% stimulation of NEE night in December 1999 and 2000, respectively, was largely due to a 26% and 28% stimulation of R below in the respective periods, because R below constituted ca. 87% of NEE night . The 37% and 42% stimulation of R above in December 1999 and 2000, respectively, was less than the 65% and 80% stimulation of the aboveground biomass by elevated C a at these times. An increase in the relative amount of the aboveground biomass in woody tissue, combined with a decrease in the specific rate of stem respiration of the dominant species Quercus myrtifolia in elevated C a , was responsible for this effect. Throughout this study, elevated C a had a greater effect on carbon uptake than on carbon loss, in terms of both the absolute flux and relative stimulation. Consequently, for this scrub–oak ecosystem carbon sequestration was greater in the elevated C a during this 2‐year study period.

Cross validation of open‐top chamber and eddy covariance measurements of ecosystem CO 2 exchange in a Florida scrub‐oak ecosystem - Sabina Dore; Graham J. Hymus; David P. Johnson; C. R. Hinkle; Riccardo Valentini; Bert G. Drake (Global Change Biology, 2003)
Simultaneous measurements of net ecosystem CO 2 exchange (NEE) were made in a Florida scrub‐oak ecosystem in August 1997 and then every month between April 2000 to July 2001, using open top chambers (NEE O ) and eddy covariance (NEE E ). This study provided a cross validation of these two different techniques for measuring NEE. Unique characteristics of the comparison were that the measurements were made simultaneously, in the same stand, with large replicated chambers enclosing a representative portion of the ecosystem (75 m 2 , compared to approximately 1–2 ha measured by the eddy covariance system). The value of the comparison was greatest at night, when the microclimate was minimally affected by the chambers. For six of the 12 measurement periods, night NEE O was not significantly different to night NEE E , and for the other periods the maximum difference was 1.1 µ mol m − 2 s − 1 , with an average of 0.72 ± 0.09 µ mol m − 2 s − 1 . The comparison was more difficult during the photoperiod, because of differences between the microclimate inside and outside the chambers. During the photoperiod, air temperature (T air ) and air vapour pressure deficits (VPD) became progressively higher inside the chambers until mid‐afternoon. In the morning NEE O was higher than NEE E by about 26%, consistent with increased temperature inside the chambers. Over the mid‐day period and the afternoon, NEE O was 8% higher that NEE E , regardless of the large differences in microclimate. This study demonstrates both the uses and difficulties associated with attempting to cross validate NEE measurements made in chambers and using eddy covariance. The exercise was most useful at night when the chamber had a minimal effect on microclimate, and when the measurement of NEE is most difficult.

Seasonal variability in the effect of elevated CO 2 on ecosystem leaf area index in a scrub‐oak ecosystem - Graham J. Hymus; Jean‐Yves Pontailler; Jiahong Li; Peter Stiling; C. Ross Hinkle; Bert G. Drake (Global Change Biology, 2002)
We report effects of elevated atmospheric CO 2 concentration ( C a ) on leaf area index (LAI) of a Florida scrub‐oak ecosystem, which had regenerated after fire for between three and five years in open‐top chambers (OTCs) and was yet to reach canopy closure. LAI was measured using four nondestructive methods, calibrated and tested in experiments performed in calibration plots near the OTCs. The four methods were: PAR transmission through the canopy, normalized difference vegetation index (NDVI), hemispherical photography, and allometric relationships between plant stem diameter and plant leaf area. Calibration experiments showed: (1) Leaf area index could be accurately determined from either PAR transmission through the canopy or hemispherical photography. For LAI determined from PAR transmission through the canopy, ecosystem light extinction coefficient ( k ) varied with season and was best described as a function of PAR transmission through the canopy. (2) A negative exponential function described the relationship between NDVI and LAI; (3) Allometric relationships overestimated LAI. Throughout the two years of this study, LAI was always higher in elevated C a , rising from, 20% during winter, to 55% during summer. This seasonality was driven by a more rapid development of leaf area during the spring and a relatively greater loss of leaf area during the winter, in elevated C a . For this scrub‐oak ecosystem prior to canopy closure, increased leaf area was an indirect mechanism by which ecosystem C uptake and canopy N content were increased in elevated C a . In addition, increased LAI decreased potential reductions in canopy transpiration from decreases in stomatal conductance in elevated C a . These findings have important implications for biogeochemical cycles of C, N and H 2 O in woody ecosystems regenerating from disturbance in elevated C a .

Elevated atmospheric CO 2 lowers herbivore abundance, but increases leaf abscission rates - Peter Stiling; Maria Cattell; Daniel C. Moon; Anthony Rossi; Bruce A. Hungate; Graham Hymus; Bert Drake (Global Change Biology, 2002)
Increased levels of atmospheric carbon dioxide (CO 2 ) are likely to affect the trophic relationships that exist between plants, their herbivores and the herbivores' natural enemies. This study takes advantage of an open‐top CO 2 fertilization experiment in a Florida scrub oak community at Kennedy Space Center, Florida, consisting of eight chambers supplied with ambient CO 2 (360 ppm) and eight chambers supplied with elevated CO 2 (710 ppm). We examined the effects of elevated CO 2 on herbivore densities and levels of leaf consumption, rates of herbivore attack by natural enemies and effects on leaf abscission. Cumulative levels of herbivores and herbivore damage were significantly lower in elevated CO 2 than in ambient CO 2 . This may be because leaf nitrogen levels are lower in elevated CO 2 . More herbivores die of host plant‐induced death in elevated CO 2 than in ambient CO 2 . Attack rates of herbivores by parasitoids are also higher in elevated CO 2 , possibly because herbivores need to feed for a longer time in order to accrue sufficient nitrogen (N), thus exposing themselves longer to natural enemies. Insect herbivores cause an increase in abscission rates of leaves throughout the year. Because of the lower insect density in elevated CO 2 , we thought, abscission rates would be lower in these chambers. However, abscission rates were significantly higher in elevated CO 2 . Thus, the direct effects of elevated CO 2 on abscission are greater than the indirect effects on abscission mediated via lower insect densities. A consequence of increased leaf abscission in elevated CO 2 is that nutrient deposition rates to the soil surface are accelerated.

Acclimation of photosynthesis and respiration to elevated atmospheric CO 2 in two Scrub Oaks - Graham J. Hymus; Tom G. Snead; David P. Johnson; Bruce A. Hungate; Bert G. Drake (Global Change Biology, 2002)
For two species of oak, we determined whether increasing atmospheric CO 2 concentration ( C a ) would decrease leaf mitochondrial respiration (R) directly, or indirectly owing to their growth in elevated C a , or both. In particular, we tested whether acclimatory decreases in leaf‐Rubisco content in elevated C a would decrease R associated with its maintenance. This hypothesis was tested in summer 2000 on sun and shade leaves of Quercus myrtifolia Willd. and Quercus geminata Small. We also measured R on five occasions between summer 1999 and 2000 on leaves of Q. myrtifolia . The oaks were grown in the field for 4 years, in either current ambient or elevated (current ambient + 350 µmol mol −1 ) C a , in open‐top chambers (OTCs). For Q. myrtifolia , an increase in C a from 360 to 710 µmol mol −1 had no direct effect on R at any time during the year. In April 1999, R in young Q. myrtifolia leaves was significantly higher in elevated C a —the only evidence for an indirect effect of growth in elevated C a . Leaf R was significantly correlated with leaf nitrogen (N) concentration for the sun and shade leaves of both the species of oak. Acclimation of photosynthesis in elevated C a significantly reduced maximum RuBP‐saturated carboxylation capacity ( V c max ) for both the sun and shade leaves of only Q. geminata . However, we estimated that only 11–12% of total leaf N was invested in Rubisco; consequently, acclimation in this plant resulted in a small effect on N and an insignificant effect on R. In this study measurements of respiration and photosynthesis were made on material removed from the field; this procedure had no effect on gas exchange properties. The findings of this study were applicable to R expressed either per unit leaf area or unit dry weight, and did not support the hypothesis that elevated C a decreases R directly, or indirectly owing to acclimatory decreases in Rubisco content.

Elevated atmospheric CO 2 stimulates aboveground biomass in a fire‐regenerated scrub‐oak ecosystem - Paul Dijkstra; Graham Hymus; Debra Colavito; David A. Vieglais; Christina M. Cundari; David P. Johnson; Bruce A. Hungate; C. ROSS Hinkle; Bert G. Drake (Global Change Biology, 2002)
The effect of elevated atmospheric CO 2 concentration ( C a ) on the aboveground biomass of three oak species, Quercus myrtifolia , Q. geminata , and Q. chapmanii , was estimated nondestructively using allometric relationships between stem diameter and aboveground biomass after four years of experimental treatment in a naturally fire‐regenerated scrub‐oak ecosystem. After burning a stand of scrub‐oak vegetation, re‐growing plants were exposed to either current ambient (379 µL L −1 CO 2 ) or elevated (704 µL L −1 CO 2 ) C a in 16 open‐top chambers over a four‐year period, and measurements of stem diameter were carried out annually on all oak shoots within each chamber. Elevated C a significantly increased aboveground biomass, expressed either per unit ground area or per shoot; elevated C a had no effect on shoot density. The relative effect of elevated C a on aboveground biomass increased each year of the study from 44% (May 96–Jan 97), to 55% (Jan 97–Jan 98), 66% (Jan 98–Jan 99), and 75% (Jan 99–Jan 00). The effect of elevated C a was species specific: elevated C a significantly increased aboveground biomass of the dominant species, Q. myrtifolia , and tended to increase aboveground biomass of Q. chapmanii , but had no effect on aboveground biomass of the subdominant, Q. geminata . These results show that rising atmospheric CO 2 has the potential to stimulate aboveground biomass production in ecosystems dominated by woody species, and that species‐specific growth responses could, in the long term, alter the composition of the scrub‐oak community.

Effects of elevated atmospheric CO 2 on root decomposition in a scrub oak ecosystem - John J. Dilustro; Frank P. Day; Bert G. Drake (Global Change Biology, 2001)
The effects of elevated atmospheric CO 2 on fine root decomposition over a 828‐day period were investigated using open top chambers with both ambient and elevated (700 ppm) CO 2 treatments in an oak–palmetto scrub ecosystem at Kennedy Space Center, Florida. Carbon dioxide enrichment of the chambers began 15 May 1996. The experiment included roots grown in ambient and elevated carbon dioxide. Vertical litterbags installed in September 1996 in each elevated and ambient chamber incubated from December 1996 to December 1998 showed no significant treatment effect on fine root or rhizome mass loss. Initial fine root percentage mass loss varied from 10.3% to 13.5% after three months; 55.5% to 38.3% of original mass had been lost after 828 days. A period of nitrogen immobilization occurred in both fine roots and rhizomes in the elevated CO 2 incubation, which is a potential mechanism for nitrogen conservation for this system in an elevated CO 2 world .

Effects of elevated atmospheric CO 2 concentration on C and N pools and rhizosphere processes in a Florida scrub oak community - Marcus Schortemeyer; Paul Dijkstra; Dale W. Johnson; Bert G. Drake (Global Change Biology, 2000)
Summary The effect of elevated atmospheric CO 2 concentration (C a ) on soil carbon and nitrogen accumulation and soil microbial biomass and activity in a native Florida scrub oak community was studied. The plant community, dominated by Quercus myrtifolia Willd. and Q. geminata Small, was exposed for 2 years to elevated C a in open‐top chambers. Buried subsoil bags were retrieved after 1 year of exposure to elevated C a . In addition, soil cores were taken twice from the chambers within two weeks in July 1998 (the first after a long dry spell and the second after 25 mm of rainfall) and divided into rhizosphere and bulk soil. Soil organic matter accumulation (excluding roots) into the buried subsoil bags was lower in elevated than in ambient C a . Concentrations of soluble carbon and ninhydrin‐reactive nitrogen (N ninh ) in the rhizosphere soil were reduced by elevated C a for the first sampling date and unaffected for the second sampling date. Microbial activity, measured as fluorescein diacetate (FDA) hydrolysis, decreased in elevated C a for the first sampling date. Microbial biomass carbon and nitrogen in the bulk soil were unaffected by elevated C a . There was no effect of elevated C a on bacterial numbers in the rhizosphere.

Elevated CO 2 increases nitrogen fixation and decreases soil nitrogen mineralization in Florida scrub oak - Bruce A. Hungate; PauL. Dijkstra; DalE. W. Johnson; C. RosS. Hinkle; BerT. G. Drake (Global Change Biology, 1999)
Summary We report changes in nitrogen cycling in Florida scrub oak in response to elevated atmospheric CO 2 during the first 14 months of experimental treatment. Elevated CO 2 stimulated above‐ground growth, nitrogen mass, and root nodule production of the nitrogen‐fixing vine, Galactia elliottii Nuttall. During this period, elevated CO 2 reduced rates of gross nitrogen mineralization in soil, and resulted in lower recovery of nitrate on resin lysimeters. Elevated CO 2 did not alter nitrogen in the soil microbial biomass, but increased the specific rate of ammonium immobilization (NH 4 + immobilized per unit microbial N) measured over a 24‐h period. Increased carbon input to soil through greater root growth combined with a decrease in the quality of that carbon in elevated CO 2 best explains these changes. These results demonstrate that atmospheric CO 2 concentration influences both the internal cycling of nitrogen (mineralization, immobilization, and nitrification) as well as the processes that regulate total ecosystem nitrogen mass (nitrogen fixation and nitrate leaching) in Florida coastal scrub oak. If these changes in nitrogen cycling are sustained, they could cause long‐term feedbacks to the growth responses of plants to elevated CO 2 . Greater nitrogen fixation and reduced leaching could stimulate nitrogen‐limited plant growth by increasing the mass of labile nitrogen in the ecosystem. By contrast, reduced nitrogen mineralization and increased immobilization will restrict the supply rate of plant‐available nitrogen, potentially reducing plant growth. Thus, the net feedback to plant growth will depend on the balance of these effects through time.

The influence of atmospheric CO2 enrichment on plant-soil nitrogen interactions in a wetland plant community on the Chesapeake Bay - Roser Matamala; Bert G. Drake (Plant and Soil, 1999)

Short‐term decomposition of litter produced by plants grown in ambient and elevated atmospheric CO 2 concentrations - S. BALL; BERT DRAKE (Global Change Biology, 1997)
The effects of elevated atmospheric CO 2 (ambient + 340 μmol mol –1 ) on above‐ground litter decomposition were investigated over a 6‐week period using a field‐based mesocosm system. Soil respiratory activity in mesocosms incubated in ambient and elevated atmospheric CO 2 concentrations were not significantly different ( t ‐test, P > 0.05) indicating that there were no direct effects of elevated atmospheric CO 2 on litter decomposition. A study of the indirect effects of CO 2 on soil respiration showed that soil mesocosms to which naturally senescent plant litter had been added (0.5% w/w) from the C 3 sedge Scirpus olneyi grown in elevated atmospheric CO 2 was reduced by an average of 17% throughout the study when compared to soil mesocosms to which litter from Scirpus olneyi grown in ambient conditions had been added. In contrast, similar experiments using senescent material from the C 4 grass Spartina patens showed no difference in soil respiration rates between mesocosms to which litter from plants grown in elevated or ambient CO 2 conditions had been added. Analysis of the C:N ratio and lignin content of the senescent material showed that, while the C:N ratio and lignin content of the Spartina patens litter did not vary with atmospheric CO 2 conditions, the C:N ratio (but not the lignin content) of the litter from Scirpus olneyi was significantly greater ( t ‐test; P 2 (105:1 compared to 86:1 for litter derived from Scirpus olneyi grown under ambient conditions). The results suggest that the increased C:N ratio of the litter from the C 3 plant Scirpus olneyi grown under elevated CO 2 led to the lower rates of biodegradation observed as reduced soil respiration in the mesocosms. Further long‐term experiments are now required to determine the effects of elevated CO 2 on C partitioning in terrestrial ecosystems.